Together and apart: inhibition of DNA synthesis by connexin-43 and its relationship to transforming growth factor β - Jeyaraman, Maya M.; Fandrich, Robert; Kardami, Elissavet (Frontiers in Pharmacology, 2013)
The membrane and channel protein Connexin-43 (Cx43), as well as the cytokine transforming growth factor (TGF) beta, suppress proliferative growth in cardiomyocytes and other cell types. Previously we showed that the inhibitory effect of Cx43 is cancelled when Cx43 becomes phosphorylated at serine (S) 262 in response to mitogen stimulation. We have now asked if the TGFbeta-triggered inhibition of DNA synthesis is associated with changes in Cx43 phosphorylation at S262. Conversely, we investigated if inhibition of DNA synthesis by overexpressed Cx43 is dependent on engaging TGFbeta signal transduction. We report that TGFbeta acutely prevented mitogen-induced Cx43 phosphorylation at S262, while chronic inhibition of TGFbeta signal transduction raised baseline levels of endogenous phospho-S262-Cx43 without affecting total Cx43. Inhibition of baseline TGFbeta signal transduction through, (a) inhibiting TGFbeta receptor I with SB431542, (b), inhibiting TGFbeta receptor II by overexpressing dominant-negative TGFbetaRII, (c), inhibiting the downstream signaling mediator Smad2 by overexpressing dominant-negative Smad2, each separately increased baseline cardiomyocyte DNA synthesis, but could not reverse DNA synthesis inhibition by overexpressed Cx43. It is suggested that inhibition of cardiomyocyte DNA synthesis by TGFbeta/TGFbetaRI/II/ phospho-Smad2 signaling is mediated, at least in part, by reducing endogenous phospho-S262-Cx43 levels.